Alih Pengetahuan Tenaga Kerja Asing (Tka) di Indonesia (Ditinjau dari Aspek Regulasi dan Kebijakannya) - Muhammad Nahyan Zulfikar; Basri Basri; Jefrie Maulana; Muharrir Muharrir (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
Arrangements for Foreign Workers are regulated in Law Number 13 of 2003 concerning Manpower which is basically intended for certain jobs or positions that cannot be occupied by local workers and to accelerate the human development index (HDI) needed to support and improve field competence for local Indonesian workers through Knowledge Transfer and Technology or which is often referred to as the transfer of knowledge and technology by means of transferring skills from foreign workers to local workers through their field education and training, in terms of accepting foreign workers in Indonesia, this cannot be separated from the General Agreement on Trade in Services (GATS)/ WTO as the rules of the WTO game that wants policies without discrimination in all aspects. This study uses the juridical-normative legal research method. As for the Juridical-Normative approach, it uses all the methods and techniques that are often used in legal research studies, namely through a statutory approach (statute approach, case approach) to see cases of the entry of Foreign Workers in Indonesian, a comparative approach to compare regulations between one country and another and the last approach, namely, a conceptual approach in the form of views that can be elaborated in solving the issues faced by foreign workers at this time. However, Indonesia must also be careful in observing WTO rules by looking at the GAST/WTO Provisions concerning the natural movement of persons. It also needs to be adopted in the policy of placing foreign workers by taking into account experience and its application in other countries in the interest of protecting Indonesian workers and not using services. foreign workers who do not have good work skills.